Doing Cross-Cultural Research
XXXI, 310 p.
Keywords: Conducting cross-cultural research is rife with methodological, ethical and moral challenges. Researchers are challenged with many issues in carrying out their research with people in cross-cultural arenas. In this book, I attempt to bring together salient issues for the conduct of culturally appropriate research. The task of undertaking cross-cultural research can present researchers with unique opportunities, and yet dilemmas. The book will provide some thought-provoking points so that our research may proceed relatively well and yet ethical in our approach. The subject of the book is on the ethical, methodological, political understanding and practical procedures in undertaking cross-cultural research. The book will bring readers through a series of questions: who am I working with? What ethical and moral considerations do I need to observe? How should I conduct the research which is culturally appropriate to the needs of people I am researching? How do I deal with language issues? How will I negotiate access? And what research methods should I apply to ensure a successful research process? The book is intended for postgraduate students who are undertaking research as part of their degrees. It is also intended for researchers who are working in cross-cultural studies and in poor nations.